Immediate post placental insertion of intrauterine contraceptive device at caesarean delivery: a prospective study - Mukka, Sravani; Y., Madhavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In India almost 65% of the women have an unmet need for family planning in the first postpartum year. Increasing rates of institutional deliveries creates an opportunity for providing quality post-partum family planning services. Post-partum Intrauterine contraceptive device (PPIUCD), a form of long acting reversible contraception (LARC) is one of the most affective and safest method available. The present study aims at evaluating the safety, efficacy, rate of acceptance and rate of discontinuation of Intra caesarean inserted contraceptive device Copper T-380A. Methods: This was a prospective study conducted at ESIC Medical College, Sanathnagar in women delivered by caesarean section during the period between March 2018 to February 2019. Recruitment was done based on the WHO medical eligibility criteria (MEC) for PPIUCD and also their willingness to participate in the study. Follow-up visits were scheduled at 6 weeks, 3 months and 6 months. Results: Of the 265 women fulfilling the WHO MEC, 180 (67.92%) were willing to participate in the study. Total acceptance rate was 67.7%. Majority of them belonged to the age group 21-30 years (80%) and para 2 (53.88). 93.3% of the women were literates. 12 (6.66%) cases lost to follow up and the complications were studied in the rest 168 women. During follow up -38.69% had missing strings, 12.5% menstrual disturbances, 4.76% abdominal pain and spontaneous expulsion in 4.1%. No cases of perforation and pregnancy were reported. Total continuation rate was 84%. Conclusions: PPIUCD is a safe and convenient option of contraception with low expulsion rates and high continuation rates.